Mechanistic Performance Enhancement of Rap Mixtures Using Treated WCO Rejuvenator: Marshall Stability and Wheel Tracking Assessment - Sepriyanna, Irma; Putranto, Leksmono S.; Subagio, Bambang Sugeng; Najid (Journal of Cultural Analysis and Social Change, 2025)
The increasing demand for sustainable pavement technologies has accelerated the adoption of high reclaimed asphalt pavement (RAP) contents; however, excessive stiffness and oxidation of aged RAP binders often limit mixture performance. This study evaluates the mechanistic performance enhancement of RAP asphalt mixtures rejuvenated using treated waste cooking oil (TWCO), with particular emphasis on Marshall characteristics and rutting resistance. Asphalt concrete wearing course (AC–WC) mixtures containing 0%, 40%, and 60% RAP were designed at their respective optimum binder contents. Marshall stability, flow, and Marshall Quotient were evaluated, while permanent deformation behaviour was assessed using a wheel tracking machine at 60 °C for 1,260 loading passes. The results demonstrate that TWCO effectively restores aged RAP binder functionality, enabling high RAP incorporation without compromising mechanical performance. Marshall stability increased from 1,395 kg for the control mixture to 1,625 kg and 1,623 kg for RAP40–TWCO and RAP60–TWCO mixtures, respectively, while flow values remained within specification limits. Marshall Quotient increased by more than 20%, indicating enhanced structural stiffness. Rutting performance improved substantially, with rut depth decreasing from 4.30 mm (control) to 2.05 mm and 2.39 mm for RAP40–TWCO and RAP60–TWCO mixtures, respectively, accompanied by significantly higher dynamic stability. Overall, the findings confirm that TWCO is an effective and sustainable rejuvenator capable of restoring aged RAP binder while preserving high-temperature stiffness and rutting resistance. The RAP40–TWCO mixture exhibited the most balanced performance, supporting the application of treated WCO in high-performance and environmentally responsible pavement design.